A review of China's municipal solid waste (MSW) and comparison with international regions: Management and technologies in treatment and resource utilization. (15th April 2021) - Ding, Yin; Zhao, Jun; Liu, Jia-Wei; Zhou, Jizhi; Cheng, Liang; Zhao, Jia; Shao, Zhe; Iris, Çağatay; Pan, Bingjun; Li, Xiaonian; Hu, Zhong-Ting
Abstract: Although municipal solid waste (MSW) has a potential risk for human health and ecological environment, it is gradually considered as one of the most renewable resources. To maximize resource utilization of MSW and its elimination, numerous efforts have been devoted worldwide to develop a systematic MSW management coupled with technologies in treatment and resource utilization (TTRU). This paper mainly focuses on MSW in eight eastern coastal regions in China on the aspects of background information (MSW generation, population, gross domestic product (GDP)/gross regional product (GRP)), related laws (acts, regulations), MSW characteristics (composition, separation, collection, transport) and TTRU. Besides, emerging technologies in MSW resource utilization for waste-to-energy (WtE) and waste-to-material (WtM) are reviewed for the first time. Finally, a comparison based on above information is conducted between China and selected developed regions, namely Berlin, Tokyo, and Singapore. The findings for China are summarized as follows: (1) MSW generation keeps a strong increasing trend especially in Guangdong, Jiangsu, Shandong, Zhejiang, and Fujian provinces, while MSW generation shows spatiotemporal variation in eastern coastal cities, provinces, and special zones; (2) MSW composition characteristics is complicated with a >50% moisture content and is dominated by 52.8–65.3% kitchen waste, 3.5–11.9% paper, and 9.9–19.1% rubber & plastics; (3) MSW management system needs to be optimized in China; (4) The MSW is treated by 52% landfill, 45% incineration and 3% composting technologies and utilization efficiency in China is much lower than that of developed countries; (5) Advanced and emerging technologies for MSW resource utilization are required and several potential WtE and WtM technologies are listed. Eventually, (6) Recommendations for developing an optimal system integrating MSW management with enhanced TTRU are presented, and technology transfer potentials from Berlin, Tokyo, and Singapore are noted. Graphical abstract: Schematic diagram showing the MSW generation in China's eastern coastal provinces and their provincial capital cities (or special zones) in 2018 associated with their spatial distribution, composition and characteristics. Image 1 Highlights: Municipal solid waste (MSW) characteristics and related laws are discussed. Emerging technologies in waste-to-energy and waste-to-material are reviewed. A comparison is conducted between Chinese provinces and selected developed regions. Integrated MSW management and treatment and utilization technologies are suggested.